ASSA14-03-24 CREG1 upregulates Rab7 expression to activate autophagy and ameliorate cardiac damage. (1st December 2014) - Song, HX; Yan, CH; Li, Y; Tian, XX; Zhu, N; Zhang, J; Sun, MY; Han, YL
Abstract : Background: In cardiomyocytes subjected to stress, autophagy activation is a critical survival mechanism that preserves cellular energy status while degrading damaged proteins and organelles. However, little is known about the mechanisms that govern this autophagic response. Cellular repressor of E1A genes (Creg1) is an evolutionarily conserved lysosomal protein, and an important new factor in regulating tissue homeostasis that has been shown to antagonise injury of tissues or cells. Recent studies showed that CREG1 is a lysosomal protein that undergoes proteolytic maturation by lysosomal cysteine proteases in the course of its biosynthesis. CREG1 contains a mannose 6-phosphate (M6P) recognition marker, and depends on interactions with M6P receptors for efficient delivery to lysosomes. CREG1 is implicated in the regulation of lysosome functions. In the present study, we aimed to investigate the regulatory role of CREG1 in cardiac autophagy, and to clarify autophagy activation mechanisms. Methods: Male heterozygous Creg1 +/− mice were generated and bred at the Southern model animal centre. Age-matched male transgene-negative wild-type (WT) littermates were used as controls. Two- to six-week-old Creg1 +/− and WT mice were subjected to an infusion of Ang II (2.5 g/kg per day) for 28 days. In another series of experiments (reversal experiment), 4-week-old male Creg1 +/− mice were subjected to an infusion of AngII for 28 days, meanwhile was treated with recombinant CREG1 protein (5 mg/kg per day, IP injections) or with chloroquine (5 or 10 mg/kg per day) for 14 days (starting day 1 and continuing until day 14). To measure fibrosis, Masson's trichrome staining was performed on paraffin sections for all experimental animals. To measure autophagic flux, western blot for analyses of LC3-II and p62 levels was employed on the myocardium samples. RT-PCR was adopted for the total RNA. Primary culture of cardiac myocytes and Adenoviral Infection were all used in this study. Results: We generated a Creg1 haploinsufficiency (Creg1 +/− ) mouse model, and identified that Creg1 deficiency aggravates myocardiac fibrosis in response to ageing or angiotensin II (Ang II). Conversely, exogenous infusion of recombinant Creg1 protein completely reversed cardiac damage. Creg1 deficiency in Creg1 +/− mouse hearts showed a marked accumulation of autophagesomes that acquired LC3II and beclin-1, and a decrease in autophagic flux as indicated by the level of p62. Inversely, restoration of Creg1 activity activated cardiac autophagy. Furthermore, chloroquine, an inhibitor of lysosomal acidification, was used to confirm that Creg1 protected the heart tissue against Ang II-induced fibrosis by activating autophagy. Using adenoviral infection of primary cardiacmyocytes, overexpression of Creg1 with concurrent resveratrol treatment significantly increased autophagy, while silencing Creg1 blocked the resveratrol-induced autophagy. Conclusions: These results suggest that rapid, Creg1-induced activation of autophagy is required to maintain heart function in the face of stress-induced myocardial damage. Both in vitro and in vivo studies identified that Creg1 deficiency reduced the expression of Rab7, thereby influencing the maturation of lysosomes and the formation of autophagolysosomes and imparing autophagy. These findings also suggest that activating autophagy via Creg1 may be a viable therapeutic strategy for improving cardiac performance under pathologic conditions.